Haynes' Baptist cyclopaedia: or dictionary of Baptist biography, antiquities, history, chronology, theology, polity and literature : to which is added a supplement, containing : an historical gazetteer... of Baptist churches... societies and institutions ... - Haynes, Thomas Wilson (Baptism controversy collection, 1848)
Vol. 1 : Aa-Fo. (No more published.)